A Decade of Business Continuity Management Practices in Oman: A Bibliographic Analysis - Al Hashimi, Hashim Mohammed Salim; Baidi , Nasrudin Bin (Journal of Ecohumanism, 2024)
This bibliometric analysis explores the evolution of Business Continuity Management (BCM) studies in Oman in the last ten years regarding publishing trends, co-authorship, and emerging topics. Based on the data collected primarily from Scopus databases, the analysis of 69 articles was augmented by The Lens and Dimensions datasets to improve the interconnectivity and metadata of the research findings. Research findings highlight an increasing trend of scholarship in BCM in Oman, with variations in yearly publications and diversified thematic concern areas, including risk management, organizational resilience, and crisis management. The leadership and linkages map revealed that specific individuals and research groups were influential and active in advancing BCM in Oman. Referring to the global literature, Oman is a relatively recent addition to the BCM research within the context of the Middle East. The study highlights the importance of BCM in increasing organizational readiness and preparedness in the face of Economic risks and disruptions, particularly in Oman, as proposed research implications and practical implications for future studies.